1996
DOI: 10.1002/j.1460-2075.1996.tb00537.x
|View full text |Cite
|
Sign up to set email alerts
|

A new Drosophila Ca2+/calmodulin-dependent protein kinase (Caki) is localized in the central nervous system and implicated in walking speed.

Abstract: Calcium/calmodulin‐dependent protein kinases (CaM kinases) have been reported to be involved in neuroplasticity. We have cloned a new Drosophila CaM kinase gene named caki. We describe the molecular characterization of caki and a behavioral effect of its elimination. The caki gene is extremely large; comparison of the genomic and cDNA sequences reveals that the caki transcription unit is at least 150 kb. The catalytic domain of this new CaM kinase protein shares homology (41%) with type II CaM kinases, while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
75
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 57 publications
1
75
0
Order By: Relevance
“…This line contains a P{EPgy2} insertion in the first intron of the CASK gene at cytological position 3R(93F12) (Spradling et al 1999;Bellen et al 2004). The CASK deficiency lines Df(3R)x307 and Df(3R)x313 (Martin and Ollo 1996) were maintained over TM6Tb-UbGFP and crossed together to generate the transheterozygote null fly 307/313 (as verified by absence of markers and GFP). Df(3R)exel6187 (Parks et al 2004) was maintained over TM6bTb and verified by the absence of the humoral marker.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This line contains a P{EPgy2} insertion in the first intron of the CASK gene at cytological position 3R(93F12) (Spradling et al 1999;Bellen et al 2004). The CASK deficiency lines Df(3R)x307 and Df(3R)x313 (Martin and Ollo 1996) were maintained over TM6Tb-UbGFP and crossed together to generate the transheterozygote null fly 307/313 (as verified by absence of markers and GFP). Df(3R)exel6187 (Parks et al 2004) was maintained over TM6bTb and verified by the absence of the humoral marker.…”
Section: Methodsmentioning
confidence: 99%
“…One such phenotype is a defect in synaptic plasticity; flies lacking CASK were defective in courtship habituation, which is thought to be mediated via interaction with CaMKII (Lu et al 2003). Loss of CASK also produces a gross locomotor deficit (Martin and Ollo 1996;Sun et al 2009), but the cellular circuitry affected by loss of CASK has not yet been identified. Flies missing the CASK gene also show abnormally long responses to stimulation of the giant fiber pathway, the multisynaptic behavioral circuit that underlies the adult escape response (Zordan et al 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of MAGUKs with these domains were described, but CASK is the only MAGUK that contains an additional large N-terminal domain with homology to calcium/ calmodulin-dependent protein kinase II␣ (3). CASK was independently discovered in vertebrates because it binds to neurexins, cell-adhesion molecules with a possible function in synapse formation (3), in Drosophila (where it is called CamGUK) because its mutation causes a behavioral phenotype (4), and in Caenorhabditis elegans (where it is called lin-2) because its mutation induces abnormal vulva development (5).…”
mentioning
confidence: 99%
“…A significant decrease in phagocytosis was observed in tsl mutant females compared to tsl D /+ heterozygous controls after infection with either E. coli (unpaired t-test, P , 0.001) or S. aureus (P = 0.038) pHrodo bacterial particles (Figure 3). To confirm that this defect was due to loss of tsl, we also measured phagocytic ability in female flies trans-heterozygous for tsl D and a deficiency line that removes tsl, Df caki (Martin and Ollo 1996;Grillo et al 2012). The tsl D /Df caki flies also phagocytosed significantly fewer E. coli and S. aureus than the controls (P , 0.001; Figure 3).…”
Section: Resultsmentioning
confidence: 90%